VD_FINDINFO AP / 2010 / 3 vom 14. September 2009 - VD Tribunal cantonal (2009)
ORDONNANCE DE RENVOI, PRÉPARATION DE LA DÉFENSE, CONSTATATION DES FAITS | 353 CPP, 411 let. g CPP, 411 let. h CPP, 433a CPP